2020
DOI: 10.1038/s41598-020-58501-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Anthropogenic Climate Change on Calcifying Plankton

Abstract: Widely regarded as an imminent threat to our oceans, ocean acidification has been documented in all oceanic basins. Projected changes in seawater chemistry will have catastrophic biotic effects due to ocean acidification hindering biogenic carbonate production, which will in turn lead to substantial changes in marine ecosystems. However, previous attempts to quantify the effect of acidification on planktonic calcifying organisms has relied on laboratory based studies with substantial methodological limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…These authors discovered that shells of modern Globigerina bulloides are about a third lighter than those from the sediments, consistent with reduced calcification induced by ocean acidification in the Anthropocene. Their results were recently confirmed by Fox et al (2020), who observed shell thinning when comparing planktonic foraminifera specimens collected from historical (HMS Challenger, 1872-1876 to recent (Tara Oceans, 2009 plankton samples. Large collections of surface sediment samples, both modern and historical (Rillo et al, 2019), are available to study, providing an opportunity to quantify anthropogenic impacts on the composition of a range of marine ecosystems and on traits of their constituent species.…”
Section: Microfossils and The Brave New Anthropocenementioning
confidence: 63%
“…These authors discovered that shells of modern Globigerina bulloides are about a third lighter than those from the sediments, consistent with reduced calcification induced by ocean acidification in the Anthropocene. Their results were recently confirmed by Fox et al (2020), who observed shell thinning when comparing planktonic foraminifera specimens collected from historical (HMS Challenger, 1872-1876 to recent (Tara Oceans, 2009 plankton samples. Large collections of surface sediment samples, both modern and historical (Rillo et al, 2019), are available to study, providing an opportunity to quantify anthropogenic impacts on the composition of a range of marine ecosystems and on traits of their constituent species.…”
Section: Microfossils and The Brave New Anthropocenementioning
confidence: 63%
“…These findings emphasize the importance of acquiring long term high-resolution time series of biological, physical and geochemical evidence in the oceans, and in particular in remote, under-studied locations or environments such as oligotrophic seas. Moreover, this and comparable studies provide baseline values that are particularly important in light of global climate trends and anthropogenic stressors that are already driving significant changes in PF calcification rates and global distribution patterns [6][7][8][9] . Supplementary Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Each run of 30 samples was accompanied by 10 reference carbonates and 2 control samples. The results are reported with reference to the international standard VPDB and the precision is b etter than +/-0.06 per mil for δ 13 C and +/-0.08 per mil for δ 18 Ο.…”
Section: Oxygen Stable Isotope Determinationmentioning
confidence: 99%
“…The stability in the foraminifera shell weights is briefly interrupted midway through Termination II, w here elevated weights are recorded. In order to understand this feature we used standard geochemical analyses (δ 18 O, Mg/Ca) for a set of samples that we combined with high resolution X-ray computed tomography (CT) to evaluate potential changes in the thickness of foraminifera shells [13] along with other biometric characteristics. The geochemical analyses confirmed the relationship between shell mass and water density, which is further supported by the μCT data that indicate clay contamination as the cause of the elevated shell weights.…”
Section: Introductionmentioning
confidence: 99%